The beauty of a woman : a comparative study on metaphorical expressions in English & Chinese poems by male poets - Loke, Sue-Ann Jia Xin (2018)
This study presents a comparative analysis on metaphorical expressions of female beauty used by male poets in English and Chinese. Female beauty is a common subject in poetry and many male poets have featured beautiful women in their works. In addition, metaphor is a poetic device that is often used in poems. Thus, it would be interesting to explore metaphors of female beauty through poetry. Poems are chosen through purposive sampling. Related metaphorical expressions are extracted from the selected poems for analysis. When comparing metaphorical expressions of female beauty cross-linguistically, congruent metaphors were discovered. These similarities are potentially the results of cultural factors and patriarchal ideology.